2019
DOI: 10.1177/0278364919880273
|View full text |Cite
|
Sign up to set email alerts
|

Imitation learning for agile autonomous driving

Abstract: We present an end-to-end imitation learning system for agile, off-road autonomous driving using only low-cost on-board sensors. By imitating a model predictive controller equipped with advanced sensors, we train a deep neural network control policy to map raw, high-dimensional observations to continuous steering and throttle commands. Compared with recent approaches to similar tasks, our method requires neither state estimation nor on-the-fly planning to navigate the vehicle. Our approach relies on, and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 32 publications
0
80
0
Order By: Relevance
“…In this context, end2end learning is defined as developing and training a complex neural network to directly map input sensory data to vehicle commands [ 10 ]. The authors of Reference [ 11 ] present an end-to-end imitation learning system for off-road autonomous driving by using only low-cost onboard sensors, having their DNN policy trained for agile driving on a predefined obstacle-free track. Since self-driving cars must manage roads with complex barriers and unclear lane borders, this strategy restricts the applicability of their system to autonomous driving.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, end2end learning is defined as developing and training a complex neural network to directly map input sensory data to vehicle commands [ 10 ]. The authors of Reference [ 11 ] present an end-to-end imitation learning system for off-road autonomous driving by using only low-cost onboard sensors, having their DNN policy trained for agile driving on a predefined obstacle-free track. Since self-driving cars must manage roads with complex barriers and unclear lane borders, this strategy restricts the applicability of their system to autonomous driving.…”
Section: Related Workmentioning
confidence: 99%
“…Recent years have witnessed a growing trend in applying deep learning techniques to autonomous driving, especially in the areas of End2End learning, as in the methods proposed by Pan et al, 3 Fan et al 7 and Bojarski et al, 2 as well as in DRL. Relevant algorithms for self-driving based on DRL can be found in the works of Kiran et al, 8 Kendal et al, 4 and Wulfmeier et al 9 Flavors of machine learning techniques have also been encountered in more traditional control approaches, such as NMPC, the uncertainty aware NMPC of Lucia and Karg 10 and the learning controllers of Ostafew et al 11 and McKinnon and Schoellig.…”
Section: Related Workmentioning
confidence: 99%
“…As shown in the deep learning for autonomous driving survey of Grigorescu et al, 1 the driving functions are traditionally implemented as perceptionplanning-action pipelines. Recently, approaches based on End2End learning from Bojarski et al 2 and Pan et al, 3 or the deep reinforcement learning (DRL) shown by Kendall et al 4 have also been proposed although mostly as research prototypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An imitation learning based procedure for high-speed off-road driving tasks is proposed by Pan et al [ 74 ], where the policy to be mimicked is provided by a model predictive controller. The learned control policy is modeled by a deep neural network made up of two sub-networks: a CNN (fed with RGB images) and a feedforward network with a fully connected layer (fed with wheel speeds).…”
Section: End-to-end Approachesmentioning
confidence: 99%